Recent progress in NP-Based Enhanced oil Recovery: Insights from molecular studies - Mohammad Yusuf; Syahrir Ridha; Hesam Kamyab (Elsevier BV, 2024)
In recent decades, nanotechnology has emerged as a rapidly growing field with diverse applications in industries such as pharmaceuticals, energy, and engineering. One of the key areas of interest is the use of nanoparticles (NPs) and nanofluids (NFs) in Enhanced Oil Recovery (EOR) to improve oil recovery efficiency. NPs offer several benefits in the hydrocarbon industry and have been shown to enhance oil and gas production. In EOR, NPs play a crucial role by interacting with the rock/oil system, optimizing conditions for oil retrieval. They offer a cost-effective and eco-friendly alternative compared to conventional methods. This comprehensive study delves into the diverse range of NPs and nanomaterials utilized in the petroleum industry, detailing their classification, characterization, and inherent properties. It explores multiple applications of NPs in chemical, thermal, and microbial flooding, elucidating the involved mechanisms like wettability modification and mobility control. Moreover, the research examines the utilization of NPs in EOR through image-based modeling, a groundbreaking approach in enhancing EOR techniques. It highlights the considerable progress achieved in EOR through the application of NPs and nanofluids (NFs). Additionally, the study assesses the potential of NPs in image-based modeling and their implications for future EOR applications, indicating a promising trajectory for integrating NPs into the petroleum industry.